2022
DOI: 10.4103/apc.apc_93_22
|View full text |Cite
|
Sign up to set email alerts
|

Strain in children with MIS-C and acute COVID-19

Abstract: Context: Cardiac injury has been described in both acute COVID-19 and the multisystem inflammatory syndrome in children (MIS-C). Echocardiographic strain has been shown to be a sensitive measure of systolic function. Aims: We sought to describe strain findings in both the groups on initial presentation and follow-up. Settings and Design: A retrospective study analyzing echocardiograms of all patients presenting with acute COVID-19 infection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…Abnormal strain measurements with preserved LVEF, during the acute phase of MIS-C and in different follow-up periods, have been also described in previous studies [ 4 , 17 , 23 , 41 ]. The above findings are suggestive of subclinical myocardial injury, that can be recognized with STE with LV-GLS analysis, but not with conventional echocardiographic parameters like the LVEF [ 11 ].…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Abnormal strain measurements with preserved LVEF, during the acute phase of MIS-C and in different follow-up periods, have been also described in previous studies [ 4 , 17 , 23 , 41 ]. The above findings are suggestive of subclinical myocardial injury, that can be recognized with STE with LV-GLS analysis, but not with conventional echocardiographic parameters like the LVEF [ 11 ].…”
Section: Resultssupporting
confidence: 75%
“…These manifestations include ventricular dysfunction, valvular dysfunction, pericardial effusion, arrhythmias, conduction disorders, Coronary Artery Abnormalities (CAA) and in severe cases acute heart failure and cardiogenic shock [5,11,[14][15][16]. From the above, the most common cardiac finding in MIS-C, is Left Ventricular (LV) systolic myocardial dysfunction, which may range from subclinical myocardial injury to severe dysfunction [5,11,13,16,17]. Within days to weeks from the acute illness, the cardiac manifestations, that are described in this syndrome, usually resolve and conventional echocardiographic parameters like the LV Ejection Fraction (LVEF) return to normal, especially after the administration of effective treatment [14,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal strain measurements with preserved LVEF, during the acute phase of MIS-C and in different follow-up periods, have been also described in previous studies [4,17,23,37]. The above ndings are suggestive of subclinical myocardial injury, that can be recognized with STE with LV-GLS analysis, but not with conventional echocardiographic parameters like the LVEF [11].…”
Section: Discussionsupporting
confidence: 68%
“…Whether we should adopt a uniform, regular evaluation in every post-MIS-N heart, including strain echocardiographic study, may be considered as reported by Minocha and Krishna. [ 7 8 ] Whether continuous administration of immune suppressants like steroids early anakinra or infliximab would have altered the natural history of chronic myocarditis is a point to ponder. The presence of fibrosis in cMRI is an independent predictor of cardiac events and sudden arrhythmogenic death.…”
Section: Discussionmentioning
confidence: 99%